2020
DOI: 10.1007/s13312-020-1962-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated Hemophagocytic Lymphohistiocytosis and Coagulopathy: Targeting the Duumvirate

Abstract: has emerged as a pandemic, claiming over 350,000 lives worldwide. Disease mortality has been mostly attributed to viral pneumonia, complicated by acute respiratory distress syndrome (ARDS) and/or sepsis. A cytokine storm like picture in peripheral blood, as evident by significantly higher plasma levels of interleukin (IL)-2, IL-7, tumor necrosis factor-α (TNF-α), granulocyte colonystimulating factor (GCSF), monocyte chemoattractant protein-1 (MCP-1), inducible protein 10 (IP 10) and macrophage inflammatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Fifth, hypertriglyceridemia as a result of lipoprotein lipase inhibition by TNF-α is not usually reported in COVID-19. Finally, though serum ferritin is increased in viral infections, including SARS-Cov2 infection, it rarely raises more than 2000 ng/ml except in the final stages of the disease [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, hypertriglyceridemia as a result of lipoprotein lipase inhibition by TNF-α is not usually reported in COVID-19. Finally, though serum ferritin is increased in viral infections, including SARS-Cov2 infection, it rarely raises more than 2000 ng/ml except in the final stages of the disease [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HScore may help to decide which patients may benefit from immune-modulators such as high-dose steroid, interleukin (IL)-1, or IL-6 blockade by anakinra or tocilizumab [ 5 ]. However, the use of HScore for COVID- 19 patients has remained questionable by some authors due to limitations regarding body temperature, raised ferritin levels (in early phase ferritin concentrations hardly reach the HScore threshold of 2000 ng/mL), leukopenia (the HScore is unable to distinguish between lymphocytopenia and neutropenia), and the lack of published data on characteristic features [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not find this score to be an independent predictor for severe disease in multivariate analysis. In a study by Bhattacharjee et al, it was stated that the HScore can be used to determine the time to initiate immunotherapy in patients with severe COVID-19 infection 6,32 . A recent study showed that high HScore values were more indicative of MAS patients than severe COVID-19 patients (201.9 ± 15.3 vs. 88.8 ± 48.3, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…An important drug that its administration may be associated with thrombocytopenia is heparin __ which is usually prescribed to COVID-19 patients as prophylaxis for thrombosis [110] . When it comes to heparin and thrombocytopenia, the first mechanism is the induction of heparin-induced thrombocytopenia (HIT).…”
Section: Pathophysiology For Thrombocytopenia In Covid-19mentioning
confidence: 99%